Common stocks and uncommon profits and other writings : 2nd edition - Fisher, Philip A. (Gildan Audio, 2019)
Widely respected and admired, Philip Fisher is among the most influential investors of all time. His investment philosophies, introduced almost forty years ago, are not only studied and applied by today's financiers and investors, but are also regarded by many as gospel. This book is invaluable for investors and has been since it was first published in 1958. This updated edition retains the investment wisdom of the original edition and includes the perspectives of the author's son Ken Fisher, an investment guru in his own right, in an expanded preface and introduction.